2015
DOI: 10.1016/j.jcps.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The median split: Robust, refined, and revived

Abstract: In this rebuttal, we discuss the comments of Rucker, McShane, and Preacher (2015) and McClelland, Lynch, Irwin, Spiller, and Fitzsimons (2015). Both commentaries raise interesting points, and although both teams clearly put a lot of work into their papers, the bottom line is this: our research sets the record straight that median splits are perfectly acceptable to use when independent variables are uncorrelated. The commentaries do a good job of furthering the discussion to help readers better develop their ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
138
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(140 citation statements)
references
References 55 publications
0
138
0
2
Order By: Relevance
“…The dichotomization was deemed to yield robust and reliable findings because multicollinearity was not present in the data (VIF 1.0-1.7 that is < 3; Iacobucci et al 2015aIacobucci et al , 2015b. The two emerging groups were compared on obsessive passion, harmonious passion, exercise intensity, and REA scores using a two (group) by two (gender) by four (dependent measures) MANOVA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dichotomization was deemed to yield robust and reliable findings because multicollinearity was not present in the data (VIF 1.0-1.7 that is < 3; Iacobucci et al 2015aIacobucci et al , 2015b. The two emerging groups were compared on obsessive passion, harmonious passion, exercise intensity, and REA scores using a two (group) by two (gender) by four (dependent measures) MANOVA.…”
Section: Resultsmentioning
confidence: 99%
“…Low and high exercise volume groups, as well as exercise intensity groups, were created by using median splits. While dichotomization is criticized in the literature (Irwin and McClelland 2003), two recent re-evaluations, based on full simulation studies, have demonstrated that the practice is robust and reliable (Iacobucci et al 2015a(Iacobucci et al , 2015b. Given that no pre-selection was done for either exercise volume or exercise intensity, dichotomization was the only method to examine possible differences between the high-low categories of these variables.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…For a between-subjects factor, we used privacy concern (based on a median split (Lacobucci et al 2015) (Median = 5.75)) to compose two groups: low (N = 19) and high (N = 21). The results revealed significant effects of personalization level (all F's > 3.4, all p's < .039) for all three advertising effectiveness variables.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative and applied strategy for estimating the influence of a particular exercise on actual sport performance is analyzing the data provided by the median split technique [21,22]. By using this calculation, researchers can suitably group the athletes according to their physical capacities, defining the “lower and upper bounds of performances” in a series of functional tests.…”
Section: Introductionmentioning
confidence: 99%